PID CONTROLLER DESIGN FOR DC MOTOR POSITION ANALYSIS AND APPLICATION TO ANKLE REHABILITATION SYSTEM - Azizi, M.A.R.; Osman, K.; Jaafar, A.; Suzumori, K. (Journal of Advanced Manufacturing Technology (JAMT), 2021)
Sprain ankle rehabilitation is a therapeutic exercise to recover ankle strength and maintain the muscles. Recently, Direct Current (DC) motors are widely used in rehabilitation exercise applications as the mechanism’s joint of a system. The DC motors allow the desired maximum and minimum range of motion during the therapist exercise. However, the control system is not stable enough for the position response of the DC motor. The objective of this study is to the purpose of the modeling control of DC motor using the Proportional-Integral-Derivative (PID) controller algorithm. The control system algorithm has been realized with implementation of PID controller for more efficient speed and position control. The PID controller is applied to analyze the performance using MATLAB software. The proposed results are compared to the performance of the system between with or without the PID controller. Based on the result obtained, the modelling controller design increased the rising time with 60.54%, settling time with 65.43% and maintained the steady-state error with zero overshoot percentage. This system using DC motor with PID controller tune is expected to improvise the motorized rehabilitation device for the immerged system technology of the robotic revolution.